EXTRACTION OF ROBUSTA COFFEE BEANS (Coffea canephora) FROM WONOSOBO BY ULTRASONIC WAVES AND ANTICANCER TESTS - Akhmad Endang Zainal Hasan; Novi Fajar Utami; Mona . (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2022)
Wonosobo Robusta coffee beans are one of the natural source ingredients that potentially could be used as ananticancer. It contains polyphenolic compounds such as chlorogenic acid, flavonoids, and hydroxy hydroquinone. Thisresearch aims to determine the optimum conditions for the extraction temperature and time of the Ultrasonic-Assisted Extraction (UAE) method on the extract yield and to determine the anticancer activity. Extraction optimizations wereanalyzed using Response Surface Methodology (RSM) with Central Composite Design (CCD) experimental design on atemperature factor of 40, 50, 60 ºC and extraction times of 10, 30 and 50 minutes. Determination of anticancer activitywas conducted using the Methyl Thiazole Tetrazolium (MTT) Assay method against MCF-7 cells. The optimization results indicate that the temperature of 52.74 ºC and time of 29,53 min are the optimum conditions for extraction with an extract yield of 9,16%. The anticancer activity test result at a concentration of 400 µg/mL is 83,25% so it has the potential to be used as an anticancer.